2021
DOI: 10.3390/pharmaceutics13030350
|View full text |Cite
|
Sign up to set email alerts
|

Taro Lectin Can Act as a Cytokine-Mimetic Compound, Stimulating Myeloid and T Lymphocyte Lineages and Protecting Progenitors in Murine Bone Marrow

Abstract: Taro (Colocasia esculenta) corm is traditionally consumed as a medicinal plant to stimulate immune responses and restore a health status. Tarin, a taro lectin, is considered responsible for the immunomodulatory effects of taro. In the present study, in order to investigate the effects of tarin on bone marrow hematopoietic population, murine cells were stimulated with tarin combined with a highly enriched conditioned medium containing either IL-3 or GM-CSF. Cells challenged with tarin proliferated in a dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In this Special Issue, we also expanded our knowledge on plant-derived compounds with a role in modulating key targeted cellular signaling pathways. An interesting study by Bertozzi and coworkers has shown that taro lectin can promote immunomodulatory effects by acting as a cytokine-mimetic compound [ 20 ]. On the other hand, Lee and coworkers reported that schisandrol A exhibits estrogen-like properties by promoting estrogenic activity via the estrogen receptor α-dependent signaling pathway [ 21 ].…”
mentioning
confidence: 99%
“…In this Special Issue, we also expanded our knowledge on plant-derived compounds with a role in modulating key targeted cellular signaling pathways. An interesting study by Bertozzi and coworkers has shown that taro lectin can promote immunomodulatory effects by acting as a cytokine-mimetic compound [ 20 ]. On the other hand, Lee and coworkers reported that schisandrol A exhibits estrogen-like properties by promoting estrogenic activity via the estrogen receptor α-dependent signaling pathway [ 21 ].…”
mentioning
confidence: 99%